Kisah Kesetiaan Bhisma Pada Hastinapura: Fenomena Pergeseran Etika Deontologi Menuju Teleologi - Puspo Renan Joyo (Jurusan Dharma Acarya STAHN-TP Palangka Raya, 2021)
This article aims to examine the story of Bhisma's loyalty to Hastinapura from an ethical perspective. The contents of this study answer three main questions, namely: What is the description of Bhisma's loyalty to Hastinapura? What caused Bhisma's change of allegiance to Hastinapura? How did Bhisma's loyalty to Hastinapura change from an ethical perspective? This research is a library research using a qualitative approach. The material object of the study is the loyalty of Bhisma in the Mahabharata story and the formal object is ethics. Data collection in this study was conducted through document studies on primary and secondary data sources that have relevance to the research theme. The results of this study indicate that in fact Bhisma is a loyal figure. The stagnation of Bhisma's loyalty to Hastinapura was caused by the behavior of the Kauravas deviating from the values ​​of truth, a value that Hastinapura has always upheld. In the hands of the Kauravas, these values ​​have been degraded. Bhisma's attitude which ultimately chose to be 'unfaithful' to Hastinapura is a form of Bhisma's loyalty in another definition, a true definition of loyalty, namely 'faithfulness to the truth'. From an ethical perspective, Bhisma's attitude shows an ethical shift, from deontological ethics to teleological ethics.